2008
DOI: 10.1017/s0020818308080089
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Complex Evolution of Norms: The Rise of International Election Monitoring

Abstract: Given that states have long considered elections a purely domestic matter, the dramatic growth of international election monitoring in the 1990s was remarkable+ Why did states allow international organizations and nongovernmental organizations~NGOs! to interfere and why did international election monitoring spread so quickly? Why did election monitoring become institutionalized in so many organizations? Perhaps most puzzling, why do countries invite monitors and nevertheless cheat? This article develops a rigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(69 citation statements)
references
References 25 publications
(3 reference statements)
0
67
0
2
Order By: Relevance
“…Jordan illustrates the foreign-aid mechanism+ King Abdullah II, who ascended in 1999, "has actively pursued stronger alliances and aid ties with the United States, Britain, and the European Union as well as international financial institutions such 59+ See Hyde 2008;and Kelley 2008+ as the IMF and the World Bank+" 60 Jordan's continued economic development hinges on privatization, foreign investment, and, especially, Western aid+ For example, since 1964, Jordan's central government annual current expenditures have closely tracked external aid receipts+ 61 Over the same time period, foreign aid as a percentage of Jordanian central government budget expenditures hovered at around 25 percent~and never below 10 percent!+ Jordan's ties with the West strengthened after 11 September 2001, when Jordan became a key supporter of the U+S+ "war on terror+" In this context, Abdullah sought to improve the status of women in society and thereby burnish Jordan's image abroad+ One way to accomplish this was by setting aside six of the 110 seats in parliament for women in 2003+ 62 The quota resulted in six female MPs but also some opposition+ In the past, Jordanian women had campaigned unsuccessfully for a quota+ 63 When Abdullah endorsed the quota by royal decree, however, he angered both the Higher Committee for the Coordination of National Opposition Parties, which issued a statement rejecting it, and also some female activists, who found that the quota discriminated against the urban areas where they lived+ 64 It is worth underscoring how this theory differs from previous research on the impact of norms in world politics+ 65 Constructivist approaches argue that norm entrepreneurs socialize global audiences to new principled ideas that then become accepted and institutionalized+ The mechanisms are first, persuasion, and then, socialization, institutionalization, and demonstration+ 66 For example, in a study of the influence of norms on state behavior, Finnemore found that the social structure of the state system caused a convergence across all states in the creation of science bureaucracies, the acceptance of new rules of war, and the definition of development+ 67 This article develops a theory, however, of how norms affect states differentially due to international inequalities+ In the case of the spread of gender quotas, reserved seats for women proliferate in developing countries even as they remain off the table in many developed countries+ Indeed, actors in the democracy establishment do not use the informational techniques of transnational activists, such as symbolism, leverage, and accountability tactics+ 68 Instead, their ideas wield influence because they enjoy a privileged position in postconflict countries via peace operations and because of their perceived linkages to foreign aid, foreign investment, and international and domestic legitimacy+ …”
Section: H3: Countries That Invite International Election Monitors Tomentioning
confidence: 99%
“…Jordan illustrates the foreign-aid mechanism+ King Abdullah II, who ascended in 1999, "has actively pursued stronger alliances and aid ties with the United States, Britain, and the European Union as well as international financial institutions such 59+ See Hyde 2008;and Kelley 2008+ as the IMF and the World Bank+" 60 Jordan's continued economic development hinges on privatization, foreign investment, and, especially, Western aid+ For example, since 1964, Jordan's central government annual current expenditures have closely tracked external aid receipts+ 61 Over the same time period, foreign aid as a percentage of Jordanian central government budget expenditures hovered at around 25 percent~and never below 10 percent!+ Jordan's ties with the West strengthened after 11 September 2001, when Jordan became a key supporter of the U+S+ "war on terror+" In this context, Abdullah sought to improve the status of women in society and thereby burnish Jordan's image abroad+ One way to accomplish this was by setting aside six of the 110 seats in parliament for women in 2003+ 62 The quota resulted in six female MPs but also some opposition+ In the past, Jordanian women had campaigned unsuccessfully for a quota+ 63 When Abdullah endorsed the quota by royal decree, however, he angered both the Higher Committee for the Coordination of National Opposition Parties, which issued a statement rejecting it, and also some female activists, who found that the quota discriminated against the urban areas where they lived+ 64 It is worth underscoring how this theory differs from previous research on the impact of norms in world politics+ 65 Constructivist approaches argue that norm entrepreneurs socialize global audiences to new principled ideas that then become accepted and institutionalized+ The mechanisms are first, persuasion, and then, socialization, institutionalization, and demonstration+ 66 For example, in a study of the influence of norms on state behavior, Finnemore found that the social structure of the state system caused a convergence across all states in the creation of science bureaucracies, the acceptance of new rules of war, and the definition of development+ 67 This article develops a theory, however, of how norms affect states differentially due to international inequalities+ In the case of the spread of gender quotas, reserved seats for women proliferate in developing countries even as they remain off the table in many developed countries+ Indeed, actors in the democracy establishment do not use the informational techniques of transnational activists, such as symbolism, leverage, and accountability tactics+ 68 Instead, their ideas wield influence because they enjoy a privileged position in postconflict countries via peace operations and because of their perceived linkages to foreign aid, foreign investment, and international and domestic legitimacy+ …”
Section: H3: Countries That Invite International Election Monitors Tomentioning
confidence: 99%
“…The last point also underpins, at least partly, the still under-explored 'prominence hypothesis' formulated by Finnemore and Sikkink (1997, p. 906), which states that 'Norms held by states widely viewed as successful and desirable models are thus likely to become prominent and diffuse'. Overall, the article's focus on short-term material versus long-term ideational processes strengthens and specifies the emerging but still relatively vague literature that concedes an important role to material factors in norm processes (Payne 2001, Kelley 2008, Wunderlich 2013.…”
mentioning
confidence: 73%
“…Although it has been possible to observe these processes in many instances of prolonged norm change, recent research suggests that material factors may not be discarded (Kelley 2008, Wunderlich 2013. They can take the form of material incentives, e.g.…”
Section: Conceptualizing India's Challenge To the Non-proliferation Normmentioning
confidence: 99%
“…Instead, we examine how these governments comply with international anti-trafficking norms by focusing on the anti-trafficking policies they pass. While most scholarship focuses on the agency of international actors and norm entrepreneurs (Sundstrom 2005;Towns 2012), or examines the causal mechanisms that determine why governments comply (Checkel 2001;Kelley 2008;Moravcsik 2000), other studies have examined key aspects of norm transfer, including the type and nature of venues in which norms are negotiated (Coleman 2011). Although there are some notable exceptions, the localization of anti-trafficking norms within Africa is made easier by the preexisting anti-slavery sentiments found throughout Africa.…”
Section: Anti-trafficking Norm Diffusion and Adaptationmentioning
confidence: 99%